S14 Lung cancer risk profiles and eligibility of attendees in a lung cancer screening demonstration pilot. (15th November 2017) - Ruparel, M; Dickson, JL; Quaife, SL; Bhowmik, A; Taylor, MN; Ahmed, A; Shaw, PJ; Burke, S; Soo, MJ; Devaraj, A; Navani, N; Duffy, SW; et al.
Abstract : Introduction: Lung cancer screening by Low-Dose CT (LDCT) has been shown to reduce mortality, and the harm-benefit balance of screening is optimised by screening those at higher risk. The Lung Screen Uptake Trial is a UK based randomised controlled trial of standard versus enhanced invitation methods for LDCT screening in more deprived communities. Methods: Patients aged 60 to 75, at higher risk of lung cancer by virtue of their recorded smoking history, were invited to a 'lung health check appointment' on behalf of their GP. Attendees at one of two secondary care sites, underwent a nurse consultation that included a lung cancer risk assessment. Participants were eligible for LDCT if they met any of the following three criteria: NLST-like criteria* (≥30 pack-year smoking history and given up ≤15 years ago); PLCOm2012 score ≥1.51%; or LLP score ≥2.5%. This abstract focuses on the performance of the different eligibility criteria. Results: At the time of analysis, 1997 individuals had been invited to screening and 936 attended and were enrolled into the study. 854 participants were eligible for LDCT by fulfilling any of the 3 criteria above, and 718 went on to have LDCT. The mean age of participants was 66.0 (SD 4.16), 54.4% were male and the mean smoking pack-year history was 39.7 (SD 24.9). After a median of 9.7 months follow up, 17 lung cancers were confirmed. Ten suspicious pulmonary nodules are undergoing diagnostic work up under the lung cancer multidisciplinary team (MDT) and 80 indeterminate nodules are under CT surveillance. The distribution of these cancers and nodules by eligibility criteria is shown in Table 1 . Conclusions: Using the NLST-like* criteria to determine eligibility would mean the fewest number screened, with 4 fewer cancers detected. The PLCOm2012 score was the most reliable way to detect cancers and resulted in less individuals screened than with use of the LLP score. Further follow up and review of the data is required to fully establish the most effective tool for determining eligibility into LDCT screening though the PLCOm2012 score shows the most promise with the available data.